Biotinylated naringenin intensified anticancer effect of gefitinib in urethane-induced lung cancer in rats: favourable modulation of apoptotic regulators and serum metabolomics. (12th November 2018) - Parashar, Poonam; Tripathi, Chandra Bhushan; Arya, Malti; Kanoujia, Jovita; Singh, Mahendra; Yadav, Abhishek; Kumar, Amit; Guleria, Anupam; Saraf, Shubhini A.
Abstract: Co-therapy through biotin modified nanoparticles (NPs) of gefitinib (Gnb) and naringenin (Nar) was investigated for its therapeutic and synergistic potential against lung cancer. The biotin-conjugated polymeric NPs (bty-Nar/Gnb) were developed using oil in water emulsion technique and optimized using central composite design. The formulations were subjected to various in vitro (A549 cell lines) and in vivo evaluations in urethane-induced lung cancer. Co-administration of Gnb and Nar NPs displayed a significant reduction in tumour volume while restoring the biochemical parameters and serum metabolites to normal levels. Significant down-regulation of anti-apoptotic proteins (P-16, MMP-9 and Bcl-2) and up-regulation of pro-apoptotic proteins (caspase-9 and BAX) was displayed with co-therapy. This investigation demonstrated the superiority of co-therapy over individual therapy for improved therapeutic efficacy and is favourable for developing a safe, effective and targeted delivery for lung carcinoma therapy. Graphical Abstract: